On a possibility of creation of positive space charge cloud in a system with magnetic insulation of electrons - Goncharov, A.A.; Dobrovol’skii, A.M.; Dunets, S.P.; Evsyukov, A.N.; Protsenko, I.M. (Вопросы атомной науки и техники, 2009)
We describe a new approach for creation an effective, low-cost, low-maintenance axially symmetric plasma optical tools for focusing and manipulating high-current beams of negatively charged particles, electrons and negative ions. This approach is based on fundamental plasma optical concept of magnetic insulation of electrons and non-magnetized positive ions providing creation of controlled uncompensated cloud of the space charge. The axially symmetric electrostatic plasma optical lens is well-known and well developed tool where this concept is used successfully. This provides control and focusing high-current positive ion beams in wide range of parameters. Here for the first time we present optimistic experimental results describing the application of an idea of magnetic insulation of electrons for generation of the stable cloud of positive space charge by focusing onto axis the converging stream of heavy ions produced by circular accelerator with closed electron drift. The estimations of a maximal concentration of uncompensated cloud of positive ions are also made.